2020
DOI: 10.1159/000506727
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>DIAPH1</i></b> Mutation as a Novel Cause of Autosomal Dominant Macrothrombocytopenia and Hearing Loss

Abstract: Macrothrombocytopenia (MTP) is a group of rare disorders characterized by giant platelets, thrombocytopenia, and variable association with abnormal bleeding. Inherited MTP are frequently misdiagnosed as immune thrombocytopenia. Associated second-organ manifestation can help narrow down syndromic MTPs. We describe a case of autosomal dominant sensorineural hearing loss and MTP caused by a gain of function mutation in DIAPH1. This mutation causes altered megarkaryopoiesis and platelet cytoskeletal deregulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this disorder, auditory loss generally starts during the first decade of life, although there are cases with intrafamilial variability. Since the identification of a mutation in DIAPH1 as the cause of sensorineural hearing loss in a large Costa Rican family [6], more families with a dominant pedigree caused by DIAPH1 mutation have been described elsewhere in the world [11][12][13]18,19,[21][22][23][24][25][26][27]. Affected individuals present frameshift or nonsense mutations or deletions near the DAD.…”
Section: Hearing Lossmentioning
confidence: 99%
“…In this disorder, auditory loss generally starts during the first decade of life, although there are cases with intrafamilial variability. Since the identification of a mutation in DIAPH1 as the cause of sensorineural hearing loss in a large Costa Rican family [6], more families with a dominant pedigree caused by DIAPH1 mutation have been described elsewhere in the world [11][12][13]18,19,[21][22][23][24][25][26][27]. Affected individuals present frameshift or nonsense mutations or deletions near the DAD.…”
Section: Hearing Lossmentioning
confidence: 99%
“…Audiograms of our proband and family members showed a typical U-shape. Autosomal dominant deafness caused by mutations in the DIAPH1 gene can be associated with thrombocytopenia [76,77]. However, our family was lost in follow-up, and therefore we cannot rule out this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The same audiological profile has not been repeated in other families with deafness and variants in DIAPH1usually, this type of HL starts at high frequencies and progresses rapidly. It is usually accompanied by mild macrothrombocytopenia (MTP) and mild neutropenia, suggesting a syndromic character of the DIAPH1-caused HL [Stritt et al, 2016;Ganaha et al, 2017;Neuhaus et al, 2017;Bastida et al, 2018;Westbury et al, 2018;Karki et al, 2021;Rabbolini et al, 2022]. Later, it was found that the low-frequency HL phenotype in the Costa Rican family might have been associated with endolymphatic hydrops, found in one of the family members [Lalwani et al, 1998].…”
Section: Diaph1mentioning
confidence: 99%